Complete genome searches for quantitative trait loci controlling blood pressure and related traits in four segregating populations derived from Dahl hypertensive rats. - Kato, N; Hyne, G; Bihoreau, M; Gauguier, D; Lathrop, G; Rapp, J (1999)
The Dahl salt-sensitive rat is one of the principal animal models of hereditary hypertension. Genome-wide searches were undertaken to detect quantitative trait loci (QTLs) that influence blood pressure, cardiac mass, and body weight in four F2 populations derived from Dahl salt-sensitive rats and different inbred normotensive control strains of rat. We detected three QTLs associated with one or more of the phenotypes, using a stringent statistical criterion for linkage (p < 0.00003). These included a novel QTL linked to blood pressure on rat Chromosome (Chr) 12, and another QTL on rat Chr 3 linked to body weight. A QTL on rat Chr 10 for which linkage to blood pressure has been described in other crosses was found to be a principal determinant of blood pressure and cardiac mass in some but not all of the crosses examined here. Three other regions showed evidence of linkage to these phenotypes with a less stringent statistical criterion of linkage at QTLs previously reported in other studies. As part of our study, microsatellite markers have been developed for three candidate genes for investigation in hypertension, and the genes have been localized by linkage mapping. These are: the rat Gs alpha subunit (Gnas) gene, the alpha-1B adrenergic receptor (Adra1b), and the Na+, K+-ATPase beta2 subunit (Atp1b2) gene.